PERANCANGAN PETA DIGITAL WISATA KABUPATEN PASAMAN DALAM MEDIA INTERAKTIF - Gebby Rahman Danihadi Kn, Dra. Zubaidah, M.Sn., Hendra Afriwan, S. Sn., M. Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Pasaman regency is one of region in the cross of sumatra, along the regional road spreads beautiful views and unique natural scene which can be used as tourist attraction. To know the location, it is required an easy and fast media to get information in the from of digital map. This digital map design is made in order to facilitate tourist finding the location which want to visit. Apropiate methode of data analysis is SWOT analysis, becouse trough this method we can know anything that developed trough exellence and opportunity and minimize lack and threat that may come from this design.This design takes from infographics concept which convey uses interesting design elements so it cloud be easily undertood what the information provided, also use the basic color of Pasaman regency’s logo that changed to soft color so gives pleasant impression to see it main media which used in this design is interactive media and supported media such as pin, sticker, calender, poster, x banner,booklet, brochure and costumes.Keywords : Digital Maps , Pasaman District, Tourist , Interactive Media